A health and lifestyle framework for management of post covid-19 syndrome based on evidence-informed management of post-polio syndrome: a narrative review. (2nd January 2022) - Dean, Elizabeth; Olsén, Monika Fagevik
Abstract: Post covid-19 syndrome includes symptoms common to post-polio syndrome, i.e. weakness; fatigue and pain like myalgic encephalomyelitis/chronic fatigue syndrome; breathlessness; and cognitive disturbances. We conducted a narrative review to establish the basis for an evidence-informed health and lifestyle framework, that underlies the management of post-polio syndrome, as a prototype for managing post covid-19 syndrome. Multi-morbidity, the non-communicable diseases (NCDs) and their risk factors, is strongly associated with SARS-CoV-2 susceptibility and poor outcomes including death. Poliomyelitis survivors may exhibit debilitating sequelae decades after infection, thus their presentations are often confounded by limitations associated with NCDs and their risk factors. An evidence-informed health and lifestyle framework is described. Its three levels of analysis and intervention include: (1) health status; (2) lifestyle practices (smoking; nutrition; weight; sedentariness, activity/exercise; sleep; stress); and (3) the three levels of the WHO's International Classification of Functioning, Disability and Health (body structures and function consistent with the conventional biomedical approach; activity; and participation). Maximising health practices of covid-19 survivors, like poliomyelitis survivors, augments function, and strengthens immunity and patients' capacities to heal, repair, and recover; as well as reduce manifestations of NCDs and their risk factors. Avenues for future research are proposed to complement findings from clinical trials.